Pendampingan Pembuatan Hand Sanitizer Aroma Minyak Atsiri Sebagai Penunjang Pembelajaran Luring Di SMP Muhammadiyah 1 Prambanan - Kundarto, Wisnu; Ermawati, Dian Eka; Zulpadly, Muhammad Fiqri; Sasongko, Heru; Rohmani, Sholichah; Artanti, Anif Nur; Sahifah, Daswati Rofiatun (Jurnal Pengabdian UntukMu NegeRI, 2021)
The schools have been allowed for doing face-to-face learning process with many requirements.Making own hand sanitizer will help schools to keep applying health protocol beside washing hands. Essential oils have been trusted for a long time give a calm effect and reduce stres. This activity have purpose to assistance hand sanitizer production with essential oils fragrance at SMP Muhammadiyah 1 Prambanan Yogyakarta. Knowledge have been transfered by team followed with demo and training to produce hand sanitizer with lemongrass fragrance at first activity. Knowledge score was determined from pre-test and post test answer score from multiple choice questions about hand sanitizer. Follow up became the next activity to ensure school can make their own hand sanitizer independently. The result showed knowledge score was increased from 52,11 to 92,11. School also have been made hand sanitizer independently with another essential oil varians. This products were limited used for school. Communication between team and school still continues.